FEATURES OF THE DEVELOPMENT OF A CIRCULAR SOLAR FLARE - Chornogor, S N.; Kondrashova, N. N. (Одеські астрономічні публікації, 2020)
We present the results of the analysis of morphology and evolution of the circular solar flare using H-alpha images. H-alpha filtergrams were obtained with the Meudon spectroheliograph. The active region NOAA 9087 had a complex multipolar magnetic field configura- tion. New magnetic fluxes emerged during the evolution of this flare-productive active region. The high flare and surge activity was observed in the active region. According to Solar Geophysical Data (SGD) the 3N/M6.4 class solar flare occurred on July 19, 2000 at 06:37 UT, peaked at 07:23 UT and lasted 2.5 hours. Two bright kernels appeared near large positive-polarity sunspot at the beginning of the flare. In a few minutes bright kernels occurred in the center of the active region near polarity in- version line. Space solar observatory Yohkoh detected a hard X-ray (HXR) coronal source in the 13.9-22.7 keV and 22.7-32.7 keV energy bands in this location. New kernels appeared in the southern and eastern parts of the active region at the boundaries of the chromospheric network. They brightened sequentially clockwise, which may indicate a slipping reconnection. Magnetic reconnec- tion was observed in the main phase of the flare in the east- ern part of the active region. In the late flare phase arcade of post-reconnection EUV loops connected the main flare ribbon with the place of repeated reconnection. Additional heating may be required for the explanation of the long flare decay phase. Flare ribbons of the circular shape were formed. The complex magnetic configuration of the studied active re- gion and circular shape of the ribbons suggest that it had a fan-spine magnetic topology with null points. Possibly, flare ribbons are the locations of intersections of the fan quasi-separatrix layer with the chromosphere. They ap- peared as a result of heating or particle beam moving along a quasi-separatrix layer from a source in the corona.